Linearization of chromatic change in a polychromatic current transformer. - Aspey, R.A (IEEE Transactions on power delivery)
A novel electric current measurement device is described. The device uses the magnetooptic Faraday effect although it differs from existing devices in its use of chromatic modulation. The modulation method involves measurement of the variation of chromaticity produced in a Faraday sensor illuminated by a beam of polychromatic light in the direction of the applied magnetic field; the novel technique of wavelength encoding has been used as a method to extend and linearize the range of the sensor. A sensitivity of 0.26 A/√(Hz) is obtained for a line current of 3.75 kA rms. It is demonstrated that analyzer angle relative to the polarizer may be used to vary sensitivity and dynamic range. A full analysis of the effects of encoder length and analyzer angle is presented and the optimal length of encoder and analyzer angle are predicted. The effect of employing multiple reflections on sensitivity is calculated. Test data from the sensor are compared with experimental and theoretical results.